Mononucleose-Like Syndrome in a Patient with Psoriatic Arthritis - Pereira, Catia; Coelho, Joana; Costa, Joana Cascais; Fortuna, Jorge (Archives of Clinical and Medical Case Reports, 2019)
Mononucleosis-like syndrome can be caused by cytomegalovirus. Usually occurs with fever, myalgias, pharyngitis, cervical adenopathy and general malaise. Respiratory symptoms are rare. Immunocompromised patients, including those treated with immunosuppressive drugs have increased clinical severity with greater complications, which are cause of morbidity and mortality. The authors present a man with psoriatic arthritis treated with weekly injectable methotrexate that came to the emergency department and was diagnosed of a cytomegalovirus mononucleosis-like syndrome complicated by respiratory symptoms and splenic stroke. Anti-viral treatment should be performed in immunocompromised patients and clinical surveillance should be maintained because of the high risk of infection reactivation.